(untitled) (Tempo e Argumento, 2012)
In this article, we discuss the relationship between politics and this time it was established around the historiographic production about Southern Cone dictatorships of Latin America. Particularly interested analyzing the ways in which this experienced by the researchers and their relation to politics interfered in research this processes, rather than to highlight how these studies to base some acts of praxis and interfered to some extent, the historical facts themselves, dialectical relationship that also was instrumental in shaping the field of study of history, not just entering a new time frame, but also new problems and sources, expanding and diversifying their perspectives and transdisciplinary dialogues, especially around the methodological dilemmas that brought the incorporation subject in which the researchers are involved in multiple ways, some direct other indirectly, issues that often be obviated in searches of more distant objects, discussion that is not only valid but essential.